The Effect of Health Promotion Program on Perceived Self-Efficacy and Self-Care Practices among Elderly with Multimorbidity in Chiang Mai, Thailand - Wungrath, Jukkrit; Khumai, Nuttida; Phrommasen, Phinphot (UI Scholars Hub, 2022)
Multimorbidity in the elderly is a major public health issue with serious consequences. This study investigated the effects of health promotion programs on perceived self-efficacy and self-care practices among the elderly with multimorbidity using a quasi-experimental study design from February to July 2021. The study samples were the elderly from Doi Saket District, Chiang Mai Province, Thailand, selected by a multistage random sampling technique. The experimental and control groups each comprised 40 elderlies with multimorbidity. All elderly participants took part in a 12-week health promotion program. The perceived self-efficacy and self-care practices of the study samples were assessed using interviews, and the group results were compared using the independent t-test. Repeated measures analysis of variance (ANOVA) was applied at a significance level of 0.05 for three different periods. Follow-up results after the intervention showed that the experimental group had significantly higher mean scores of perceived self-efficacy and self-care practice than the control group (p-value<0.05). The health promotion program enhanced perceived self-efficacy and self-care practices in the elderly with multimorbidity. It can also be applied to improve the quality of life of people in other age groups.